Exploring jahuts views on using ICT for the preservation of cultural identity in Pahang, Malaysia - Khong, Choo Yeong; Gill, Sarjit S.; Talib, A. T.; Xue, Fang Yi (Human Resource Management Academic Research Society, 2023)
This paper aims to explore the views of the Jahut community towards Information and Communication Technology (ICT) adoption in preserving their cultural identity. Despite their substantial contribution to the diversity of human culture and knowledge, the Orang Asli communities persist in experiencing marginalization and the erosion of their traditional lifestyles. This study employed a qualitative approach, with data collected through semi-structured interviews with eleven members of the Jahut community from Pahang, Malaysia. The findings indicated that the Jahut informants hold positive views towards the adoption of ICT for cultural identity preservation. However, the findings also revealed that the concerns of the Jahut informants about the potential misuse of technologies, which could accelerate the loss of indigenous languages, customs, and knowledge. By addressing the importance of incorporating the views of the Jahut community, this study sheds light on the significance of ICT adoption for preserving their unique cultural identity in the face of rapid digital transformations.